Outsourcing African Labor Kru Migratory Workers in Global Ports, Estates and Battlefields until the End of the 19th Century - Gunn, Jeffrey (Africa in Global History, 2021)
This title structures the fragmented history of Kru workers into a coherent global framework. The migration of Kru workers in the Atlantic, Indian and Pacific Oceans, in commercial and military contexts represents a movement of free wage labour that transformed the Kru Coast into a homeland that nurtured diasporas and staffed a vast network of workplaces.